Caffeine and chlorogenic acid content of Coffea canephora cultivars in different environments - Rocha, Rodrigo Barros; Alves, Enrique Anastácio; Tadeu, Hugo Cesar [UNESP]; Teixeira, Alexsandro Lara; Bizzo, Humberto Ribeiro; Antoniassi, Rosemar; Pacheco, Sidney; Santiago, Manuela Cristina Pessanha de Araujo (Coffee Science, 2023)
Coffee plants of the Coffea canephora species are currently grown in tropical regions throughout the world, and both higher yield efficiency and higher beverage quality are important considerations. The aim of this study is to characterize the content of caffeine and chlorogenic acids of C. canephora cul-tivars in different environments. According to the maturation cycle of each clone, samples of cherry coffee were collected from ten cultivars evaluated in the environments of Porto Velho, RO; Ouro Preto do Oeste, RO; and Manaus, AM in Brazil. These environments with contrasting characteristics represent most of the coffee fields established in the Af and Aw climate types in Latossolos Vermelhos and Latossolos Amarelos typical of the Western Amazon. The results were analyzed considering the factorial design to quantify the effects of genotypes, of environments, and of the genotype × environment interaction (GE) on the caffeine and chlorogenic acid content. Despite the significant genetic-environment (GE) effects, the caffeine and chlorogenic acid content primarily exhibited genetic control. In comparison to caffeine content, chlorogenic acid content showed a stronger environmental influence, resulting in more variations in genotype performance across different environments. The significant positive association between the caffeine content and chloro-genic acid content favors the selection of plants that simultaneously have higher or lower content of both traits. The dispersion of the first two principal components, linked with reference points, enabled the identification of genotype performance across all environments in a single analysis. The selection of clone BRS3210 results in a gain from selection of 14.99% in caffeine content, while cultivation of clone BRS3193 yields a gain from selection of 10.81% in chlorogenic acid content. The selection of clone BRS2299 results in a reduction of 21.85% in caffeine content and of 9.15% in chlorogenic acid content.
Keywords: Conilon; genotype × environment interaction; robusta; western Amazon